Strategi Komunikasi Public Relations Rapi Films dalam Menciptakan Awareness Penonton Film Andai Ibu Tidak Menikah dengan Ayah - Noviya Zayeda Mattersyd; Safiani A Fararoek; Abdul Malik; Meiyanti Nurchaerani (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
The development of digital technology has transformed Public Relations (PR) practices into more dialogic and participatory forms of communication. This transformation has also influenced film promotion strategies, which increasingly emphasize audience engagement and awareness. This study aims to analyze Rapi Films’ PR communication strategy in creating audience awareness of Andai Ibu Tidak Menikah dengan Ayah. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model and the Four-Step Process of Public Relations, consisting of fact finding, planning, communicating, and evaluation. The findings indicate that Rapi Films integrated audience insights, emotional storytelling, digital communication, media relations, KOLs, community engagement, and social engagement. Audience awareness was reflected in their ability to recognize and recall the film and associate it with emotional messages concerning family relationships. The findings suggest that awareness was created through relevant, integrated, and audience-oriented communication.